(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2022)
Clinicopathological status of duck plague was investigated at different upazila of Dinajpur district during the period from October, 2017 to March, 2018. The clinical features emphasiging the mortality and prevalence, necropsy for gross morbid lesions, histopathological features were examined. The farm and flock history, managemental aspects, vaccination status, nutrition, etc. were recorded carefully. The data was collected and statistically analyzed. Farmer’s complaints about their affected birds were also considered and emphasized. The average mortality rate was recorded as 14.42% and prevalence was 19.81%. The sick birds clinically showed moderate to severe depression, ocular and nasal discharges, ataxia, dypsia. The affected organs were pathologically characterized as mild to moderate congestion and haemorrhages with misshapen, ruptured cystic ova and histopathologically characterized as mild to moderate architectural destruction, reactive cell infiltration. Asian Australas. J. Biosci. Biotechnol. 2021, 6 (3), 147-152